Plant interactions with other organisms: molecules, ecology and evolution - Austin, Amy Theresa (2014)
The plant sciences, during much of the 20th century, evolved as a group of disciplines that sought to explain plant responses to factors of the abiotic environment, such as water, mineral nutrients and light. In the last two decades, there have been major advances in our understanding of how plants interact with a growing list of other components of their biotic environment, including other plants, animal consumers and detritivores, pollinators, and beneficial and pathogenic microorganisms. This progress has rendered a much richer picture of plant function in real life than the one produced by traditional models of physiological responses to simple variations in abiotic factors. Simultaneously, this progress has revealed major gaps in our understanding of the evolution of plant adaptation, the molecular mechanisms that mediate phenotypic plasticity in complex biotic scenarios, and the ecosystem consequences of these interactions.